Microscopic structure and migration of 90° ferroelectric domain wall in BaTiO3determined via molecular dynamics simulations - Azuma, Hikaru; Ogata, Shuji; Kobayashi, Ryo; Uranagase, Masayuki; Tsuzuki, Takahiro; Durdiev, Dilshod; Wendler, Frank (Journal of Applied Physics, 2023)
BaTiO3 is a well-known piezoelectric material with commercial uses. The ferroelectric state of BaTiO3 generally comprises electrically polarized domains separated by domain walls (DWs). The DW alters local polarization vectors by an angle of 90° for 90° DW or 180° for 180° DW. The DW is crucial to piezoelectric properties such as response time and fatigue. Furthermore, the DW structure and its dynamics in BaTiO3 are not well understood. Hence, for the first time, we theoretically obtained the atomistic structure of the 90° DW via molecular dynamics simulations at 300 K with the core-shell interatomic potential, using a large-scale system with a side length of 2.8 × 10 3 Å. The width of the 90° DW thereby obtained was approximately 30 Å, which was 20 Å wider than that of the 180° DW. Under the external electric field E → ext parallel to the DW, we observed an extension of a domain having a polarization vector with a positive component along the E → ext-direction. The migration velocity of the 90° DW was approximately two times that of the 180° DW at the same E ext in the range 7 - 20 MV / m. For E ext ≥ 15 MV / m, the migration velocity of the 90° DW in the direction with a positive component along the polarization vector of the extending domain was substantially higher than that in the opposite direction. The physical causes of the difference in the migration velocities of the 90° DW in the two directions were analyzed.
CRIS-Team Scopus Importer:2023-03-24